The Influence of Dynamic Innovation Capabilities, Information Technology, and Digital Leadership on Employee Performance with Digital Workplace Dynamics as a Mediating Variable and Digital Leadership as a Moderating Variable - Setiawan, Iwan; Sunarya, Herni; Ismawati, Kun; Rauf, Abdul; Mujanah, Siti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the effect of dynamic innovation capabilities, information technology, and digital leadership on employee performance, by considering digital workplace dynamics as a mediating variable and digital leadership as a moderating variable. A quantitative approach is used with the Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis technique. The results of this study indicate that dynamic innovation capabilities, information technology, and digital leadership have a significant effect on employee performance, both directly and indirectly through digital workplace dynamics. Dynamic innovation capabilities and digital leadership are proven to be the most dominant factors in improving performance, while information technology capabilities play an important role in forming an efficient and collaborative work ecosystem. Digital workplace dynamics function as a mediator that connects innovation and technology with improved performance, although its influence is smaller than the direct effect. In addition, the role of digital leadership as a moderating variable strengthens the relationship between innovation and technology on employee performance. This means that leaders who are adaptive to technology and able to facilitate organizational change strategically contribute significantly to driving the achievement of organizational goals in the digital era. This finding emphasizes the importance of synergy between innovation, technology, and leadership in supporting performance in the digital era. The theoretical and practical implications of this study contribute to the development of digital-based human resource management strategies.